2016
DOI: 10.1371/journal.pone.0164751
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Regulatory T Cells and Altered Cytokine Profile Locally in the Airways of Young Smokers with Normal Lung Function

Abstract: Smoking influences the immune system in different ways and, hypothetically, effects on pulmonary effector and regulatory T cells emerge as potentially detrimental. Therefore, we characterized the frequencies and characteristics of CD4+ and CD8+ T cell subsets in the blood and lungs of young tobacco smokers. Bronchoalveolar lavage (BAL) and peripheral blood were obtained from healthy moderate smokers (n = 18; 2–24 pack-years) and never-smokers (n = 15), all with normal lung function. Cells were stimulated ex vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Ostadkarampour et al have reported an increased frequency of a potent suppressor Treg subset and a decreased frequency of Th17 cells in the BAL of young healthy moderate smokers with normal lung function, relative to healthy never-smokers. 39 Chronic obstructive pulmonary disease (COPD) is a lung disorder highly associated with cigarette smoking. About 90% of COPD patients are current smokers or exsmokers, and about 50% of lifelong smokers develop COPD.…”
Section: Cigarette Smokingmentioning
confidence: 99%
“…Ostadkarampour et al have reported an increased frequency of a potent suppressor Treg subset and a decreased frequency of Th17 cells in the BAL of young healthy moderate smokers with normal lung function, relative to healthy never-smokers. 39 Chronic obstructive pulmonary disease (COPD) is a lung disorder highly associated with cigarette smoking. About 90% of COPD patients are current smokers or exsmokers, and about 50% of lifelong smokers develop COPD.…”
Section: Cigarette Smokingmentioning
confidence: 99%